If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(13 + x) = 36 + x (13 * 2 + x * 2) = 36 + x (26 + 2x) = 36 + x Solving 26 + 2x = 36 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 26 + 2x + -1x = 36 + x + -1x Combine like terms: 2x + -1x = 1x 26 + 1x = 36 + x + -1x Combine like terms: x + -1x = 0 26 + 1x = 36 + 0 26 + 1x = 36 Add '-26' to each side of the equation. 26 + -26 + 1x = 36 + -26 Combine like terms: 26 + -26 = 0 0 + 1x = 36 + -26 1x = 36 + -26 Combine like terms: 36 + -26 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| Y^2-4y+8x=8+4x | | 2x-1/2y=7 | | Cos(x)=0.35 | | y=(x-2)(4x+1) | | 2y-7x=-6 | | 2.5f=12.5 | | 16=40n | | 1/7x^2=5/7x | | 24x=84 | | 10x+12x^2=0 | | 0=3x+120x^2 | | P/17=3 | | n/5-8 | | 6y+3=4y-2 | | x^2+11x+1452=0 | | COSX-SINX=4/3 | | x+18=-6x-14 | | 0.2x+8=12 | | (x).4=50000 | | 12cos^2(x)-8cos(x)+1=0 | | x-6=12+2x | | 5y-y=36 | | 132=(x+7)2+x^2 | | -8n+5=-7n-12 | | -64sin(8x)=0 | | -4(r+2)=(2-4r) | | 10x=8+4x | | 0.16(y-8)+0.08y=0.18y-1.4 | | (5t-2)(2t-3)=0 | | 0.05x+0.04(8000-x)=374 | | (15y+13)+(20y+7)=90 | | Y=x-24 |